Application of a maxillary transfacial approach to the caudal oral cavity and orbitozygomaticomaxillary complex in dogs - Thatcher, Graham P.; Congiusta, Michael C.; Soukup, Jason W. (Frontiers in Veterinary Science, 2023)
Surgical access and visualization for excision of large pathologic lesions of the orbitozygomaticomaxillary complex (OZMC) and caudal oral cavity can be a challenge in veterinary oromaxillofacial surgery and may limit one’s ability to perform such procedures. Combined intra- and extra-oral approaches as well as commissurotomy have been advocated in the past. However, each of these approaches present unique limitations specific to each approach. A transfacial approach that ameliorated these limitations could be advantageous. In this descriptive cohort study, we investigate the application and outcomes of a maxillary transfacial approach to the OZMC and caudal oral cavity in six client-owned dogs. The approach is based on the Weber-Ferguson approach for human applications and provided excellent exposure of the intended region in all six patients. We contend the maxillary transfacial approach provides some advantages to the more conventional combined intra-oral/extra-oral approach or commissurotomy for excision of large pathologic lesions of the OZMC and caudal oral cavity.